Effects of IPOB Sit-At-Home on the Economy of Ezeagu Local Government Area of Enugu State, South-Eastern Nigeria - Obi, E. Nku (NIU Journal of Humanities, 2023)
The study examined the effects of IPOB sit-at-home order on the economy of Ezeagu Local Government Area of Enugu State, the South-Eastern region of Nigeria. The study employed both primary and secondary sources of data with the use of the system theory by Talcott Parsons which states that every system is made up of sub-system that has component parts, and each component has a vital role to play for the overall performance of the system as a whole. Questionnaires were administered to respondents and data gathered were analyzed with the use of in-depth summary and coding as well as Chi-square at 0.05 level of significance. Findings revealed that IPOB sit-at-home order has negatively affected the economy of Ezeagu Local Government Area of Enugu State, south-eastern region of Nigeria. Based on the findings, the study recommends that there is need for IPOB to suspend its sit-at-home order and embrace dialogue with the Federal Government to press down their demand for the release of their leader because this sit-at-home has not yielded any positive results, rather it has deeply eaten up the economy and affected the livelihood of the people which had led to more crimes and even loss of lives and properties. Also, the distribution of resources among the six (6) geo-political zones of Nigeria should be done through proper Federal character principle as this will go a long way to reducing what the Indigenous People of Biafra (IPOB) perceived as gross marginalization to the south-eastern regions. Keywords: Indigenous People of Biafra (IPOB), National Economy, National Integration